Relative contributions of climate and land-use change to ecosystem services in arid inland basins. (20th May 2021) - Li, Jiangyue; Zhang, Chi; Zhu, Shihua
Abstract: Climate change (CC) and land-use change (LUC) have far-reaching influences on ecosystem services (ESs), which are key to human well-being. This study aimed to develop a novel hypothetical framework for not only determining the dynamic changes in ESs at the basin level but also providing robust operating rules for distinguishing the relative contributions of CC and LUC to ESs. In this study, with the Ili-Balkhash Basin (IBB) in Central Asia as the study area, the spatiotemporal changes in climate, land use and four typical ESs (i.e., water yield (WY), soil retention (SR), carbon storage (CS) and habitat quality (HQ) from 1992 to 2014 were quantified. Three comparative experiments (i.e., only CC, only LUC and CC & LUC) were designed to explore the relative contributions of CC and LUC to the four ESs. The results showed that the changes in WY (89.92%–92.42%), SC (86.45%–90.59%) and CS (70.07%–81.19%) in the CC simulation were more significant than those in the LUC simulation, whereas HQ was more affected by LUC (81.82%–97.93%) than CC. The correlation analysis revealed that precipitation (PPT) is the main driver of changes in WY (R = 0.53–0.97), SR (R = 0.26–0.57) and CS (R = 0.67–0.74) in the IBB. Furthermore, the degradation of HQ was attributed to the conversion of grassland to cropland (+13.57 × 10 3 km 2 ) and urban expansion (+140 km 2 ) from 1992 to 2014. Our findings indicate that current land-use policies should consider the relative influences of CC and LUC to balance the trade-offs among ESs. Graphical abstract: Image 1 Highlights: A novel framework to distinguish the relative contributions of climate & land-use change to ecosystem services was proposed. Water yield, soil retention and carbon storage capacity are closely related to climate change (precipitation fluctuation). Habitat quality is more easily disturbed by land use change (land use conversion). Land-use policies should give priority to the relative impacts of climate and land-use change on ecosystem services.